1998
DOI: 10.1144/gsl.qjeg.1998.031.p2.03
|View full text |Cite
|
Sign up to set email alerts
|

Point load testing of weak rocks with particular reference to chalk

Abstract: The Point Load Test (PLT) was developed as an index test to predict the Uniaxial Compressive Strength (UCS) of core too broken for UCS testing. A correlation factor ( K ) between UCS and PLT strength of 24 has been proposed although this value is disputed. This paper investigates the value of K for chalk and other weak rocks using published and unpublished data sets and concludes that K is not a unique value even for a single set of specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The uniaxial compressive strength, UCS, obtained from the correlation proposed by the ISRM (1985), is around 66 MPa. Bowden et al (1998) pointed out that the multiplying factor K (K=UCS/I S,50 ) suggested by the ISRM, on the basis of tests on hard rocks, is not suitable for this type of rock. In fact, vesiculated basalts of similar porosity give a value of K equal to 11 (Read et al 1980in Bowden et al 1998.…”
Section: Results From Previous Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The uniaxial compressive strength, UCS, obtained from the correlation proposed by the ISRM (1985), is around 66 MPa. Bowden et al (1998) pointed out that the multiplying factor K (K=UCS/I S,50 ) suggested by the ISRM, on the basis of tests on hard rocks, is not suitable for this type of rock. In fact, vesiculated basalts of similar porosity give a value of K equal to 11 (Read et al 1980in Bowden et al 1998.…”
Section: Results From Previous Testsmentioning
confidence: 99%
“…Bowden et al (1998) pointed out that the multiplying factor K (K=UCS/I S,50 ) suggested by the ISRM, on the basis of tests on hard rocks, is not suitable for this type of rock. In fact, vesiculated basalts of similar porosity give a value of K equal to 11 (Read et al 1980in Bowden et al 1998. Rotonda et al (2009) found an average value of about 6 for the Stromboli autoclastic breccia with 20% porosity.…”
Section: Results From Previous Testsmentioning
confidence: 99%
“…When the related literature is examined, it is seen that many studies examine the relationship between PLI and the physical and mechanical properties of rocks. The PLI has been the most researched test method for indirectly estimating the UCS of rocks (Bieniawski 1974(Bieniawski , 1975Bowden, Lamont-Black, and Ullyott 1998;Hawkins 1998;Rusnak and Mark 2000;Tsiambaos and Sabatakakis 2004;Akram and Bakar 2007;Sundara 2009;Singh, Kainthola, and Venkatesh, 2012;Alitalesh, Mollaali, and Yazdani, 2015;Elhakim 2015;Karaman, Kesimal, and Ersoy, 2015;Sheshde and Cheshomi 2015;Armaghani et al, 2016;Ferentinou and Fakir 2017;Kabilan, Muttharam, and Elamathi. 2017).…”
Section: Introductionmentioning
confidence: 99%